Combined Effectiveness of Nortriptyline and Topiramate in Comparison to Nortriptyline Alone as Migraine Prophylaxis - Akter, Nargis; Imran, Ahmed; Tanjum , Sumaiya; Sultana, Papiya; Afroz, Rozina; Parvin, Shahina; Sultana, Masuma; Hossain, Abul; Biswas, Ripa; Gulshan, Masrufa; Jahan, Israt; Adhikari, Santa (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Migraine is a chronic neurological illness characterized by recurrent episodes of headache and other related symptoms. Patients who experience severe headaches frequently need to use both acute and preventive medication treatments for migraine. Prophylactic treatment is intended to improve the patient's capacity to function normally, to increase the benefits of acute treatments, and to lessen the frequency, duration, or severity of attacks. Objective: The aim of this study was to compare the combined effectiveness of Nortriptyline and Topiramate in comparison to Nortriptyline alone as migraine prophylaxis. Methods: The Randomized controlled trail was conducted in the department of Pharmacology and Therapeutics, Dhaka Medical College, Dhaka, from January 2022 to December 2022. A total of 42 patients were enrolled by block random sampling block of 3, 1:1 design. The Participants were divided into two groups. The 21 patients treated with Nortriptyline were in group A and the 21 patients treated with Nortriptyline-Topiramate were in group B. Results: In this study, in both Group, highest patients in age group 20-29 years. Male: Female ratio was 1:4 and 1:3 respectively in Group A and Group B. At the end of 3rd month, headache frequency was same between two groups (0.0day/month). Median duration of headache and VAS score significantly decreased in two groups. Maximum decreased in Group B compared to Group A. There was the highest reduction of HIT-6 score in Group B (64.3±5.2 to 45.0±5.2). Conclusion: Both drugs were effective in reducing headache. Between them, Nortriptyline-Topiramate provided the best improvement. J Com Med Col Teachers Asso July 2024; 28(2): 48-52